Social cohesion and counter-terrorism a policy contradiction? - Husband, Charles 1944-; Alam, Yunis ca. 20./21. Jh (Policy Press, 2011)
This book offers a unique research-based contribution to the debate around community cohesion and counter-terrorism policies in Britain. It is an essential read for academics, policy makers and practitioners concerned with the management of ethnic diversity